How to privatize the Post Offices:: An opportunity as bridge for solution - Loenert, Francisco Martins (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
Starting from the premise that the best future to the Post Office is its privatization, the article aimed to not only seek for a solution to improve the logistic system, but simultaneously to elevate it to the highest level worldwide. Taking advantage of the ascending blockchain technology, and inspired by existing projects, we deconstructed the concept that the company which collects with the sender will necessarily be the same to deliver to the recipient. Thus, the proposed model took into account all of the current characteristics, and sought in a viable way to define a ground zero to its logistic system, offering dynamism and competition to the market.